EFEKTIVITAS PELAKSANAAN PROGRAM BACA TULIS AL QUR’AN (BTQ ) TERHADAP PENINGKATAN KEMAHIRAN BACA TULIS AL-QUR’AN PADA MAHASISWA SEMESTER III JURUSAN PENDIDIKAN AGAMA ISLAM FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Rusmin B, Muhammad; Abu Bakar, Abd. Syukur; Mosiba, Risna (Inspiratif Pendidikan, 2023)
This journal discusses "The Effectiveness of the Implementation of the BTQ Program on Increasing Reading and Writing Proficiency in the Qur'an in Semester III Students Class of 2020 majoring in Islamic Religious Education, Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar". The problems discussed in this thesis are 1. How is the Implementation of the BTQ Program to Improve Reading and Writing Al-Qur'an Proficiency in Semester III Students Class of 2020 majoring in Islamic Religious Education 2. How is the Effectiveness of the BTQ Program to Increasing Al-Qur'an Reading Proficiency in Semester III Students Class of 2020 majoring in Islamic Religious Education. This type of research is Quantitative where the data is in the form of numbers and uses statistical analysis. The population in this study were all Semester III students Batch 2020 majoring in Islamic Religious Education at the Tarbiyah and Teacher Training Faculty of UIN Alauddin Makassar, totaling 194 people. While the sample is 15% of the 30 students with the sampling technique using Random Sampling. Based on the results of collecting and processing data using descriptive statistical analysis, the authors can conclude that the implementation of the BTQ Program in improving Al-Qur'an reading and writing skills in Semester III Students Class of 2020 majoring in Islamic Religious Education, Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar is considered very effective because in practice it is in accordance with the established rules as stated by the respondent. The results of the analysis of inferential statistical testing, namely the t test, obtained the results of the hypothesis test that t_0 = 1.071 and t_table = 2.048. t_0<t_table (1.071 <2.048) then H_o is rejected H_I is accepted. Thus it can be concluded that there is a significant influence. The implementation of the BTQ program is very effective on the reading and writing ability of the Qur'an of students majoring in Islamic Religious Education, Faculty of Tarbiyah and Teacher Training, UIN Alauddin Makassar. The implications for this research are that based on the results of the research, the authors think that it is necessary to maintain and support the implementation of the BTQ program at UIN Alauddin Makassar.